Inhibition of RelA expression via RNA interference induces immune tolerance in a rat keratoplasty model. (May 2016) - Yang, Jize; Feng, Songfu; Yi, Guoguo; Wu, Wei; Yi, Ruiwen; Lu, Xiaohe; Xu, Wanfu; Qiu, Haijiang
Highlights: Immature or tolerogenic DCs were constructed with the RelA-shRNA transfection. RelA knockdown in BMDCs prolong cornea allograft survival. The corneal opacity and neovascularization scale of the lv-shRelA-DC groups were slight. RelA knockdown in BMDCs inhibit the transcriptional activity of IFN-γ, IL-10 and IL-17. p65 is critical for transactivation of inflammatory factor. Abstract: RelA, the most important regulator of NF-kB activity, and its mechanisms in keratoplasty immune rejection have not been fully investigated. In the present study, lentivirus-mediated silencing of RelA expression in a bone marrow-derived dendritic cell (BMDC) model was tested. The BMDCs were transfected with RelA-shRNA to induce an immature, maturation-resistant and tolerogenic phenotype, while not significantly changing IFN-γ, IL-10 and IL-17 expression. A fully allogeneic rat cornea transplant model was established for in vivo studies. The allograft mean survival time (MST) of lv-shRelA-DC injection groups were significantly longer than the untreated BMDC group and control group. The corneal opacity and neovascularization scale of the lv-shRelA-DC injection groups were slight compared to pair control others. Postoperative flow cytometric analysis revealed that the percentage of Treg positive cells was dramatically increased in animals that received an lv-shRelA-DC injection. ELISA and qRT-PCR analyses of serum showed that IFN-γ and IL-17 expression were suppressed by lv-shRelA-DC treatement. In vivo experiments demonstrated that IL-10 induced immunosuppression was partly attributed to injection of lv-shRelA-DC throughout the experiment, differing from the general anti-inflammatory factors. Luciferase and Chromatin IP evaluation showed that RelA knockdown in BMDCs significantly reduces DNA binding to IFN-γ, IL-10 and the IL-17 promoter and inhibited of transcriptional activity. Taken together, this study illustrates a significant role of RelA in mediating the corneal neovascularization by affecting IL-17 expression. Our comprehensive analysis shows that the significant role of RelA provides a novel and feasible therapeutic approach for the prevention of corneal allograft rejection.